A perspectiva sociocrítica da modelagem matemática: uma proposta sobre o câncer de próstata na campanha Novembro Azul - VIDAL, Edmilson de Oliveira (2023)
In this study, we will approach Mathematical Modeling from a socio-critical perspective in order to reach a critical level in discussions about prostate cancer in the context of the Blue November campaign. It is a qualitative research of an empirical nature, carried out with 30 students from the eighth year of the EMEF school - Cecília de Nazaré da Fonseca Municipal Elementary School in Salinópolis-Pa. The Mathematical Modeling proposal was conducted with the direction of the steps based on Burak (2007) and theoretically based on the conception of Barbosa (2003). As a result, we brought interdisciplinary debates, of a social nature, in the area of health and education, which addressed behavioral issues, awareness, information, statistical literacy through reading, discussion and analysis of the mathematical models involved in the unfolding of the proposal.